Features of digital socialization of primary school students in the context of different levels of Internet involvement - Pronina, Angelina N. (2020)
Nowadays, human life is greatly influenced by digitalization and informatization, which requires the reinterpretation of the matter of social formation and human development in the context of ontogenesis. From the moment of birth, a child lives in a mixed social and digital environment, which influences traditional socialization in one way or another. The researchers identify both positive and negative aspects of digital socialization of the younger generation. The authors of the present research analyzed the features of digital socialization of primary school students with different levels of Internet involvement. The experiment on the identification of Internet addiction involved 540 parents. The sample on the study of digital socialization included 316 primary school students aged 7 to 9. On the one hand, the results showed the preservation and demonstration of the content and methods of traditional socialization among younger students of all levels of Internet involvement in terms of digital socialization. This fact indicates the integration and combination of digital and traditional socialization. On the other hand, the increase in the levels of Internet involvement contributes to the replacement and transition from traditional socialization to a digital one.